The role of general and firm-specific training for new technology adoption and economic growth: a critical review - Roberto Antonietti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2005)
Aim of this article is to present an overview of the main economic literature focusing on the issue of how technology adoption and the accumulation of technical skills by firms affects the aggregate performance of economic systems. Since the analysis is labour-demand oriented, a differentiation between a 'mainstream' and a 'non-mainstream' approach is supposed to be crucial, the first being consistent with the neoclassical paradigm of the firm and human capital, while the second with the Schumpeterian paradigm and the so called view of the firm as a 'learning organization'. Going through the basic models, the paper argues that while the mainstream approach is primarily based on production costs analyses and the capacity of the market and hierarchies to provide the specific skills in order for workers to deal with new technologies, non-mainstream approaches are mainly oriented to the analysis of dynamic competition, entrepreneurial/managerial skills and within-firm organizational learning processes that are necessary in order to cope with a changing environment.
Keywords: 330; Technologiewahl; Qualifikation; Lernende Organisation; Wirtschaftswachstum; Ressourcenorientierter Ansatz; Humankapital; Theorie